S21-02 - The structure of the ultra high risk mental state for psychosis. A latent class cluster analysis study - Valmaggia, L.; Stahl, D.; Yung, A.; Nelson, B.; McGorry, P.; McGuire, P. (European psychiatry, 2011)
Individuals at Ultra High Risk (UHR) for psychosis typically present with attenuated psychotic symptoms. However it is difficult to predict which individuals will later develop frank psychosis when their mental state is rated in terms of individual symptoms. The objective of the study was to examine the phenomenological structure of the UHR mental state and identify symptom profiles that predict later transition to psychosis. Psychopathological data from a large sample of UHR subjects were analysed using latent class cluster analysis. A total of 318 individuals with a UHR for psychosis. Data were collected from two specialised community mental health services for people at UHR for psychosis: OASIS in London and PACE, in Melbourne. Latent class cluster analysis produced 4 classes: Class 1 - Mild was characterized by lower scores on all the CAARMS items. Subjects in Class 2 - Moderate scored moderately on all CAARMS items and was more likely to be in employment. Those in Class 3 - Moderate-Severe scored moderately-severe on negative symptoms, social isolation and impaired role functioning. Class 4 - Severe was the smallest group and was associated with the most impairment: subjects in this class scored highest on all items of the CAARMS, had the lowest GAF score and were more likely to be unemployed. This group was also characterized by the highest transition rate (41%). Different constellations of symptomatology are associates with varying levels of risk to of transition to psychosis.